Analisis Konsentrasi Kemiskinan di Indonesia Periode Tahun 1999-2003 - Diana Wijayanti; Heri Wahono (Economic Journal of Emerging Markets, 2005)
Poverty issues is related not only to the population of the poor but also to poverty concentration in certain areas. This research deals with concentration pattern of poverty in Indonesia analysed by Theil Entrophy index on poverty report data in 26 provinces in Indonesia 1999-2003. The analysis reveals that poverty is highly concentrated in relatively advanced provinces in Java during 1999-2003.Analysis on gap within region as well as between region in Java resulted in higher Theil index than that of other region. Overall calculation shows that there was a slightly decreasing trend in poverty concentration in 1999-2003. Contributing factors to the trend are education, health and human development quality in the region. Therefore, this research raises the urgency of reassessing the government development strategy that use to be growth oriented. Encouraging economic activities in less developed regions will contribute to economic growth and in turn increase the income of the population in the region.Keywords: poverty concentration, theil entropy index